2015
DOI: 10.1002/mnfr.201400819
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates lipopolysaccharide‐induced acute kidney injury by suppressing inflammation driven by macrophages

Abstract: Scope Acute kidney injury (AKI) is the most frequent and serious complication in sepsis, a potentially deadly inflammatory response induced by bacterial, viral or fungal infection. Lipopolysaccharide (LPS) induced AKI is associated with an abnormal inflammatory response, including renal endothelial dysfunction and renal inflammation. Resveratrol, a natural phytoalexin with low toxicity and anti-inflammatory properties, is known to protect endothelial cells and modulate the immune response in sepsis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 48 publications
(70 reference statements)
3
70
0
Order By: Relevance
“…And it has been suggested that the in vivo biological activity of equimolar doses of Pte may be greater than that of resveratrol (6), and the antioxidant activity of Pte are superior to resveratrol due to its higher lipophilicity, which increases its ability to be absorbed compared to resveratrol (6). Studies have demonstrated that resveratrol has salutary effect on sepsis-induced multiple organ dysfunction, such as myocardial depression (7), AKI (8)(9)(10). However, the effect of Pte on sepsis-induced AKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…And it has been suggested that the in vivo biological activity of equimolar doses of Pte may be greater than that of resveratrol (6), and the antioxidant activity of Pte are superior to resveratrol due to its higher lipophilicity, which increases its ability to be absorbed compared to resveratrol (6). Studies have demonstrated that resveratrol has salutary effect on sepsis-induced multiple organ dysfunction, such as myocardial depression (7), AKI (8)(9)(10). However, the effect of Pte on sepsis-induced AKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, TNF-α and Fas-ligand bind directly to tubular cell receptors, promoting the activation of caspase-8 and inducing apoptosis [21]. Furthermore, in recent experimental animal models the exposure to LPS was associated to a significant increase in vacuolar degeneration, renal cell apoptosis and neutrophils and macrophages infiltration [22][23][24][25]. In particular, Langford et al observed in vitro multiple caspase activation in rabbit kidney cells treated with LPS, suggesting the stimulation of the extrinsic, intrinsic and endoplasmatic reticulum/stress apoptotic pathways [26].…”
Section: Evaluation Of Plasma Immunemediated Moleculesmentioning
confidence: 99%
“…Resveratrol might still exhibit its beneficial effects during recovery by reduction of oxidative stress [29, 48] and suppression of inflammation at later phases than analyzed in our short term model [30, 48]. The reduction in pCysC might point towards that, but a reperfusion time aiming to answer this question is far beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 78%